An Exploration of English Students’ Perception on the Impact of Artificial Intelligence in Learning English Reading Comprehension - Fitriani Fitriani; Syakira Shalima; Shagyta Sastra Winaya; Riska Amelia; Rinu Riana; Samsul Amri (Media Akademika Publisher, 2025)
Technological advancement has significantly impacted English language learning, especially in reading skills. However, there remains a gap between the utilization of technologies such as Artificial Intelligence (AI) and a comprehensive understanding of students' perceptions of its influence. This study aims to explore the perceptions of English Department students regarding the impact of AI on enhancing their reading comprehensions. A quantitative research method with a survey design was employed, involving 21 fourth-semester students. The instrument used was a Likert-scale questionnaire covering three key indicators: selection, organization, and interpretation. The findings revealed that students held a positive perception of AI in reading, with an overall mean score of 3.14. These results indicate that AI effectively assists students in selecting appropriate reading materials, organizing information, and interpreting texts more effectively. The study concludes that AI can serve as a beneficial tool in the reading learning process, although it cannot replace the crucial role of educators in shaping character and moral values. Therefore, it is recommended that educators and researchers consider a balanced integration of AI in English language learning.